Nnedi Okorafor’s Binti: African Science Fiction and the Reimagined Black Girl - Seow, Janet Rosemarie (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2022)
Nnedi Okorafor’s Binti unsettles harmful depictions of Black childhood and reconceptualizes the role of young Black females in racialized communities with an acute awareness of the challenges they encounter in the realworld. Using the speculative form of Binti as an allegory for the present, this article turns to the character of Binti to highlight ways to overcome obstacles of exclusion and otherness. Inspiration is found in how Okorafor utilizes Africanfuturism as a framework that artfully integrates and retains African Indigenous cultures in a technologically advanced world. Additionally, childhood studies informs how this article examines the impact of Africanfuturism as a defamiliarizing strategy to address normalized (Western, white) childhood and notions of futurity for Black children and youth.